Detection and molecular characterization of lumpy skin disease and bovine papular stomatitis viruses in lumpy skin disease-suspected outbreaks in Tanzania - Fredy T. Makoga; Jelly S. Chang’a; Irene K. Meki; Charles Mayenga; Tirumala B. K. Settypalli; Stella Bitanyi; Bishop Magidanga; Emma Peter; Augustino Chengula; Giovanni Cattoli; Charles E. Lamien (Virology Journal)
Abstract Background Lumpy Skin Disease (LSD) is endemic in sub-Saharan countries and is currently a global threat to the cattle industry. Information on the circulating Capripoxvirus lumpyskinpox, formerly known as Lumpy Skin Disease Virus (LSDV), and other poxviruses infecting cattle is very scant in Tanzania. The current study aimed to confirm and characterize LSDV and other poxviruses infecting cattle, from LSD suspected outbreaks in Tanzania. Methods A total of 24 samples were collected from four LSD suspected outbreaks reported in Tanzania between February and May 2023. Samples were screened for LSDV genome by real-time PCR and then subjected to a high-resolution multiplex melting (HRM) assay where 10 samples were positive for Capripoxvirus (CaPV) and one sample was Parapoxvirus (PPV) positive. Four LSDV genes; RPO30, GPCR, EEV glycoprotein and B22R and the partial B2L gene of PPVs were analyzed. Results All targeted LSDV genes from the Tanzanian isolates showed 100% similarity and isolates clustered with commonly circulating LSDV field isolates. Furthermore, the single nucleotide polymorphism (SNP) at position 240 (A-> G) of the EEV gene differentiates the Tanzanian LSDVs from the group of ancient Kenyan LSDV isolates while the B22R sequences of the Tanzanian LSDV isolates differed from the LSDV Neethling and LSDV KSGP-0240 derived vaccines. Sequence analysis of the partial B2L gene of the Tanzanian parapoxvirus bovinestomatitis, formerly known as Bovine papular stomatitis virus (BPSV) showed a different BPSV strain circulating compared to publicly available sequences. Conclusion These findings confirm the presence of LSDV in Tanzania, which suggesting the need for establishing an effective control program and continuous monitoring. The presence of a typical profile for Tanzania BPSV is an indication that, although never reported before, BPSV is established in the country therefore this virus should be included in the differential diagnosis of LSDV.